Driven to Distraction At Work : How to Focus and Be More Productive - Hallowell, Edward M. (Boston Harvard Business Review Press, 2015)
"Hallowell, known for his work with children and adults, now identifies the underlying reasons why people really lose their ability to focus at work--where many of today's adults feel distracted and unproductive. He explains why commonly offered solutions like 'learn to manage your time better' or 'make a to-do list' just don't work because they don't address the deeper, underlying issues of mental distraction"
Include Appendix, Notes and Index
Keywords: Psychology, Industrial -- Time management -- Distraction (Psychology) -- Attention